Diversity and Antibiotic Susceptibility of Bacteria in Water of Hotel Restaurants in Dhaka City (Journal of the Asiatic Society of Bangladesh, Science, 2017)
Present study was conducted to determine the microbiological status of water from dispensers in different roadside hotel and restaurants of Dhaka city. Samples were collected from seven hotel and restaurants. Aerobic heterotrophic bacterial count ranged between 1.5 × 10 and 8.8 × 103 cfu/ml. Enteric and related bacterial abundance in MacConkey, SS and Cetrimide agar media ranged from 0 to 4.9 × 106, 0 to 2.1 × 105 and 0 to 1.2 × 106cfu/ml, respectively. In total, 28 bacterial isolates were obtained during the study period. Among them, 15 were heterotrophic isolates and 13 were enteric and related bacteria. Among 15 aerobic heterotrophic isolates, 11 were gram positive and five were gram negative. Out of 11 gram positive isolates, 7 belonged to the genus Bacillus viz. B. circulans, B. subtilis, B. stearothermophilus, B. brevis and B. cereus and one to coccus viz. Micrococcus roseus. The other gram positive species were Kurtia gibsonii, Auriobacterium liguefaciens and Curtobacterium luteum. Four gram negative isolates were Neisseria elongate sub. spp. glycolytica, Plesiomonas shigelloides, Pseudomonas fluorescens biovar 1, Pseudomonas aeruginosa. All 13 enteric and related isolates were gram negative, short rod; and non-spore formers and belonged to the genera Escherichia, Klebsiella, Shigella and Pseudomonas. Among all isolates, two were resistant and six were susceptible to all five antibiotics.Asiat. Soc. Bangladesh, Sci. 43(2): 173-180, December 2017